Synthesis and Characterization of Cellulose Acetate and Nanocellulose Acetate from Sengon Agroindustrial Waste (Paraserianthes falcataria) - Nur Ikhtiarini; Masruri MASRURI; Siti Mariyah Ulfa; Widodo Widodo (Chemistry Department, The University of Brawijaya, 2022)
Synthesis and characterization of cellulose acetate and nanocellulose acetate have been carried out. Cellulose was isolated from sengon wood powder waste using 6% NaOH solution and bleached with NaOCl. The cellulose was hydrolyzed with 60% formic acid to obtain nanocellulose. Cellulose and nanocellulose were then modified with acetic anhydride. The synthesized products were characterized by FTIR to identify organic functional groups, powder XRD to measure crystallinity, and SEM to observe surface morphology. Solubility tests in several types of solvents were also performed. The degree of substitution (DS) of cellulose acetate and nanocellulose acetate was carried out based on Indonesia’s SNI 0444:2009 method. The DS calculation show that the cellulose acetate and nanocellulose have DS of 2.9 and 2.1, respectively.